Prototype Measuring Device for Electric Load in Households Using the Pzem-004T Sensor - Partaonan Harahap; Faisal Irsan Pasaribu; Muhammad Adam (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Electrical energy has become a basic need for all people in the world, alternative energy as described above can be applied to households that are supplied by two energy sources namely energy sources from solar panels and PLN need to be accompanied by a system of regulating the supply of electric load power (control systems), so that the change of electrical energy supply to the load can work automatically. Along with the continued increase in the Basic Electricity Tariff (TDL) it is necessary to design a measurement of the use of electrical loads in households using the Pzem-004T Sensor to determine the amount of power from an electrical load and can be monitored from a certain distance. From the results of tests and measurements with various household loadings for 0 days, a very significant comparison from the previous TDL of Rp. 159,000.00, - and after using the Pzem-004T Sensor, the result of the TDL tariff calculation is Rp. 109,308.